2011
DOI: 10.1016/j.jacc.2011.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction in Patients Undergoing Cardiac Surgery

Abstract: LV diastolic dysfunction is a powerful, independent predisposing substrate for the initiation of POAF. Evaluation may be useful during risk stratification of patients undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 32 publications
5
29
1
Order By: Relevance
“…1416 In the present study, although the overall incidence of POAF in the propensity matched cohort was 53.9%, the rate of POAF among patients who underwent LAA closure was 68.6%, in comparison with 39.3% for patients who did not undergo LAA closure. Johnson and colleagues 17 performed prophylactic LAA closure in 437 patients during open heart surgery.…”
Section: Discussioncontrasting
confidence: 57%
“…1416 In the present study, although the overall incidence of POAF in the propensity matched cohort was 53.9%, the rate of POAF among patients who underwent LAA closure was 68.6%, in comparison with 39.3% for patients who did not undergo LAA closure. Johnson and colleagues 17 performed prophylactic LAA closure in 437 patients during open heart surgery.…”
Section: Discussioncontrasting
confidence: 57%
“…Another surrogate parameter is the peak A wave velocity measured by pulsed wave Doppler echocardiography that has been widely used to assess atrial function[ 19 22 ] and has been shown to be associated with AF risk in the Framingham Heart Study and the Cardiovascular Health Study[ 17 , 23 ]. Furthermore, mitral annular E/E’ has been reported as an appropriate parameter to estimate the degree of atrial remodeling[ 24 ] since diastolic dysfunction is an independent risk factor for AF[ 25 , 26 ]. Additionally, it has been shown that recurrence of AF after electrical cardioversion can be predicted by the degree of diastolic dysfunction[ 27 ] or LA dilatation[ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…55 TTE might be able to demonstrate structural changes of the heart, especially the LA, which constitutes the "substrate", while the surgery is the inevitable "trigger" (Figure 2). 56 Cardiac SPECT was used in one study of patient undergoing liver transplantation and proved able to exclude patient developing POAF. 17 As with dobutamine stress testing cardiac SPECT cannot be used in an acute setting Figure 2 With age and comorbidities, "substrate" (ie, chronic inflammation, fibrosis, etc.)…”
Section: Imagingmentioning
confidence: 99%
“…POAF might occur when patients with a "substrate" are exposed to the hemodynamic challenges of surgery and post-surgery inflammatory stress response (Figure 2). 56 The incidence of POAF ranges from 4% to 17% in abdominal surgery. This variation cannot be explained solely by age and comorbidity; indeed, some patients with comorbidity will undergo surgery at an advanced age without developing POAF.…”
Section: Predictors Of Poaf After Abdominalmentioning
confidence: 99%